Professional Training Strategy to Develop Research Skills in Tutors - Jayce Díaz Díaz; Gisela Bravo López; Yamirka González Puerto; Lisbet Menes Ortega; Esther Hernández Pérez; Zenia Tamara Sánchez García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Background: the tutor is the leading figure in the formation and development of research skills, so he should become a researcher and professor in order to train students in research. Objective: to elaborate a professional training strategy to achieve the preparation of tutors as researchers and to influence the scientific activity of students. Methods: we complemented the quantitative and qualitative methodologies. The context of the research was the Information Management in Health profile from the Bachelor in Health Technology Career of Cienfuegos Municipality during the 2009 - 2010 academic course. Empirical methods were used: document analysis, observation, survey, interviews and experts criteria. Theoretical methods included analytical-synthetic, inductive - deductive, historical, logical, generalization, and modelling systems. Results: we designed a professional training strategy structured into four phases: needs assessment of tutors related to research skills, planning the research methodology course, implementation of the strategy for improvement, and evaluation and monitoring. For validation, experts criteria as to competence coefficient was used, a process that confirmed the feasibility, relevance and quality of this strategy. Conclusions: the professional training strategy was considered to be an integrating proposal that contributes to the formation and development of research skills in tutors, taking into account the importance, novelty, feasibility and relevance of the steps and actions.